Why are there so few female entrepreneurs? An examination of gender differences in entrepreneurship using Norwegian registry data - Arvid Raknerud; Marit Rønsen (Statistics Norway, Research Department, 2014)
Women make up almost 50 percent of the employed population in Norway, but only about 25 percent of the entrepreneurs. Using registry data on the whole population we address gender differences in the propensity to become an entrepreneur. We do so by analysing transition from ordinary wage employment into entrepreneurship, defined as either sole proprietorship or owner- managed incorporated entrepreneurship. We focus on the impact of the family and household situation and show that children are no barrier to female entrepreneurship. This result holds also when we look at the establishment of an incorporated business, which represents a bigger investment decision than mere self-employment. Moreover, we find that gender differences with regard to the impact of family and household characteristics are generally smaller for incorporated entrepreneurship than for self-employment. For example, while there is a clear positive effect on women's - but not men's - propensity to become self-employed if the partner is highly educated, the impact of the partner's education is ambiguous both for men and women in the case of incorporated entrepreneurship. The strongest predictor of entrepreneurship among the partner characteristics, both for men and women, is whether or not the partner is an entrepreneur. Although our results do not bring a clear answer to why there are so few female entrepreneurs in Norway, an important insight from our analyses is that the family and household situation can be ruled out as a major explanation.
Keywords: L26; J13; J16; J22; C23; 330; : Entrepreneurship; gender; work and family; partner's characteristics; probit regression; linked registry data